1988
DOI: 10.1111/j.1475-1313.1988.tb01031.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in accommodation: a review

Abstract: When a young observer attempts to accommodate steadily on a fixed stimulus, the norminally steady‐state response shows small instabilities or fluctuations (sometimes termed microfluctuations or oscillations). These fluctuations typically have an amplitude of a few tenths of a dioptre and a frequency spectrum extending up to a few Hertz. The properties of these fluctuations are described for various viewing conditions: pupil diameter, target vergence, target form, target contrast, and target luminance all influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
194
1
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(203 citation statements)
references
References 57 publications
7
194
1
1
Order By: Relevance
“…The spectral estimator of an AR process of order is given by (6) where and are the least-square estimators of and , respectively. In Fig.…”
Section: B Frequency Domain Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral estimator of an AR process of order is given by (6) where and are the least-square estimators of and , respectively. In Fig.…”
Section: B Frequency Domain Representationmentioning
confidence: 99%
“…The results of these studies have consistently shown that during steady viewing conditions the eye constantly changes its focus (accommodation). The magnitude of these changes in accommodation are typically less than D (Diopter) and have a maximal amplitude of about 0.5 D [6]. The temporal frequencies of the accommodation fluctuations are typically less than 2 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the continuous microfluctuations of the accommodative response occur naturally over approximately a 0.25 D to 0.50 D range, producing a potential variation of up to 0.50 D between readings. 10 Microfluctuations are potentially more of a problem in autorefractor measurements, as refraction is measured in a very short period, although some allowance for this can be made by averaging a number of measurements. Another problem associated with accommodation is that some individuals exhibit an increase in the accommodation response when viewing an autorefractor target.…”
mentioning
confidence: 99%
“…Thus, the results shown here provide new insights into an eye disorder as common as presbyopia (32,33) .…”
Section: Discussionmentioning
confidence: 93%